NK1-r Antagonist Treatment Comparable to Decompressive Craniectomy in Reducing Intracranial Pressure Following Stroke - Sorby-Adams, Annabel J.; Leonard, Anna V.; Hoving, Jan W.; Yassi, Nawaf; Vink, Robert; Wells, Adam J.; Turner, Renée J. (Frontiers in Neuroscience, 2019)
Background and Purpose: The morbidity and early mortality associated with stroke is largely attributable to cerebral edema and elevated intracranial pressure (ICP). Existing pharmacotherapies do not target the underlying pathophysiology and are often ineffective in sustainably lowering ICP whilst decompressive craniectomy (DC) surgery is life-saving yet with surgical/peri-operative risk and increased morbidity in the elderly. Accordingly, there is an urgent need for therapies that directly target the mechanisms of edema genesis. Neurogenic inflammation, mediated by substance P (SP) binding to the tachykinin NK1 receptor (NK1-r), is associated with blood-brain barrier (BBB) disruption, cerebral edema and poor outcome post-stroke. NK1-r antagonist treatment ameliorates BBB dysfunction and cerebral edema in rodent stroke models. However, treatment has not been investigated in a large animal model, an important step towards clinical translation. Consequently, the current study compared the efficacy of NK1-r antagonist treatment to DC surgery in reducing ICP post-stroke in a clinically-relevant ovine model. Methods: Anaesthetized female Merino sheep (65±6 kg, 18-24 months) underwent sham surgery (n=4) or permanent middle cerebral artery occlusion (n=22). Stroke animals were randomized into one of 5 treatments: 1xNK1 bolus (4h), 2xNK1 bolus (4h;9h), 3xNK1 bolus (4h;9h;14h), DC surgery (performed at 4h) or saline vehicle. ICP, blood pressure and blood gases were monitored for 24h post-stroke. At 24h post-stroke anaesthetized animals underwent MRI, followed by perfusion and brains removed and processed for histological assessment. Results: 2xNK1, 3xNK1 administration or DC surgery significantly (p<0.05) reduced ICP compared to vehicle. 1xNK1 was ineffective in sustainably lowering ICP. On MRI, midline shift and cerebral edema were more marked in vehicles compared to NK1-r treatment groups. Conclusion: Two or 3 boluses of NK1-r antagonist reduced ICP comparable to DC surgery, suggesting it may provide a novel alternative to invasive surgery for management of elevated ICP.